Characterization of erythromycin-degrading strain Aspergillus sydowii W1 revealed by transcriptome analyses. (March 2023) - Ren, Jianjun; Lai, Biyun; Niu, Dongze; Wang, Zhenzhu; Hardie, William James; Zhi, Junqiang; Wang, Chongqing; Yu, Yicheng; Taoli, Huhe; Li, Zhijie; Jiang, Xingmei; Li, Chunyu
Abstract: Erythromycin residual, as a persistent, antibiotic pollutant, poses a serious threat to environmental and human health. Thus, developing effective technologies to eliminate erythromycin from the environment is urgent. In this study, a new fungus W1 identified as Aspergillus sydowii which can utilize erythromycin as its only carbon source was isolated from soil contaminated with erythromycin. The degradation efficiency of erythromycin by strain W1 was 84.05% within seven days under optimal conditions (30 °C, pH 6.0 and 100 mg L −1 erythromycin). The degradation pathway of erythromycin was proposed from four intermediates detected by HPLC-MS, and enzymes involved in erythromycin metabolism in strain W1 were preliminarily inferred. Notably, genomic and transcriptomic analysis also confirmed that strain W1 degrades erythromycin via glycoside hydrolase and esterase activity. This study demonstrated that A. sydowii W1 is a novel erythromycin-degrading strain, which has great potential for removing erythromycin from contaminated soils, and also provides a new perspective for other applications of this particular strain. Graphical abstract: Image 1 Highlights: A novel erythromycin-degrading fungus Aspergillus sydowii W1 was isolated from an erythromycin-contaminated sample. The expression of 855 gene was relatively upregulated under erythromycin stress. The erythromycin degradation pathway of A. sydowii W1 was illustrated based on the metabolites and transcriptomic data. The esterase and glucoside hydrolase are the key enzymes involved the biodegradation process.